2016
DOI: 10.1021/acs.jnatprod.6b00227
|View full text |Cite
|
Sign up to set email alerts
|

Leoligin, the Major Lignan from Edelweiss (Leontopodium nivale subsp. alpinum), Promotes Cholesterol Efflux from THP-1 Macrophages

Abstract: Leoligin is a natural lignan found in Edelweiss (Leontopodium nivale ssp. alpinum). The aim of this study was to examine its influence on cholesterol efflux and to address the underlying mechanism of action. Leoligin increases apo A1- as well as 1% human plasma-mediated cholesterol efflux in THP-1 macrophages without affecting cell viability as determined by resazurin conversion. Western blot analysis revealed that the protein levels of the cholesterol efflux transporters ABCA1 and ABCG1 were upregulated, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 31 publications
0
27
0
Order By: Relevance
“…In addition, the bubble map can also relate to some of the potential biological activities of lignans, e.g., estrogenic and antiestrogenic, antioxidant, anti-inflammatory, and anticancerogenic properties (Baumgartner et al, 2011;Teponno et al, 2016;Wang et al, 2016;Linder et al, 2019;Zálešák et al, 2019), especially with antioxidant and anti-inflammatory activity being identified as frequently mentioned terms, whereas they were strong interests in phytoestrogen and cancer. By limiting to "articles" (excluding other publication types such as reviews), a quick query of "clinical trial*" within the analyzed body of literature returned with 50 hits only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the bubble map can also relate to some of the potential biological activities of lignans, e.g., estrogenic and antiestrogenic, antioxidant, anti-inflammatory, and anticancerogenic properties (Baumgartner et al, 2011;Teponno et al, 2016;Wang et al, 2016;Linder et al, 2019;Zálešák et al, 2019), especially with antioxidant and anti-inflammatory activity being identified as frequently mentioned terms, whereas they were strong interests in phytoestrogen and cancer. By limiting to "articles" (excluding other publication types such as reviews), a quick query of "clinical trial*" within the analyzed body of literature returned with 50 hits only.…”
Section: Discussionmentioning
confidence: 99%
“…Within the bioactive compounds realm Santini and Novellino, 2018;Daliu et al, 2019;Durazzo et al, 2019), the class of lignans is of interest for their potential biological activities, i.e., estrogenic and antiestrogenic, antioxidant, antiinflammatory, metabolism-modulating, anti-proliferative, and anticancerogenic properties (Baumgartner et al, 2011;Teponno et al, 2016;Wang et al, 2016;Linder et al, 2019;Zálešák et al, 2019). Moreover, it is worth mentioning that the spectrum of biological activities attributed to lignans is being enlarged, i.e., related to newly discovered compounds belonged to this group (Zhang et al, 2014;Gnabre et al, 2015;Su and Wink, 2015;Hongthong et al, 2016;Azam et al, 2019;Zhuang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Quantification of cholesterol efflux was performed, as described previously . THP‐1 cells (ATCC) were maintained in RPMI‐1640 medium (Lonza) supplemented with 10% fetal bovine serum (Gibco), 100 U/mL penicillin and 100 μg/mL streptomycin, and 2 mmol/L l ‐glutamine (Invitrogen) at 37°C and 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was assessed by the resazurin conversion assay . For this assay, THP‐1 cells were seeded at 0.4×10 5 cells per well in 96‐well plates and differentiated, then loaded with unlabeled cholesterol and treated with UCB, as described in the previous section.…”
Section: Methodsmentioning
confidence: 99%
“…While Leoligin (Fig. 6) proved highly effective against thickening of the inner wall of blood vessels (Reisinger et al, 2009), an unknown terpene shows a significant cancer hostile activity against human leukemia cells (Wang et al 2007). Moreover (Hornick et al, 2008) can showed after taking an extract from the whole root an improvement in the capacity of memory and kick off a discussion for taking this extract in the prevention and treatment of dementia.…”
Section: Fig 4 Aloe Veramentioning
confidence: 99%